Comparison Of Arbitration Dispute Resolution In Business Between Indonesia And United States Of America (Journal of Private and Commercial Law, 2022)
AbstractBusiness activities always allow for a dispute between the parties involved. As a result of such disputes the parties always want a quick resolution Delays in resolving trade disputes will result in inefficient economic development, decreased productivity, and otherwise increased production costs. This not only hinders the improvement of health and progress of workers, but also harms consumers. To resolve business disputes, the parties have the freedom to choose what dispute resolution forum to choose. Business disputes that arise may not be left alone, but it is necessary to find an alternative solution appropriately so as not to be prolonged and cause substantial losses. Alternative dispute resolution is not only known in Indonesia but also in other countries, one of which is Indonesia, in this paper the author will discuss about alternative dispute resolution in the field of business between Indonesia and America. Â